3D Printing: Application of 3D Printing for Smart Objects with Embedded Electronic Sensors and Systems (Adv. Mater. Technol. 1/2016). Issue 1 (20th April 2016) - Ota, Hiroki; Emaminejad, Sam; Gao, Yuji; Zhao, Allan; Wu, Eric; Challa, Samyuktha; Chen, Kevin; Fahad, Hossain M.; Jha, Amit K.; Kiriya, Daisuke; Gao, Wei; Shiraki, Hiroshi; et al.
Abstract : In article number 1600013, Ali Javey and co‐workers demonstrate a tailored 3D printing approach that is capable of delivering fully integrated, personalized smart objects. Electronics and sensing systems with advanced capabilities are embedded in the 3D structure during printing, to provide new degrees of freedom in the electrical and mechanical design of embedded systems for wearable, medical, and soft robotics applications.